Optimizing Citrullus lanatus seed-based coagulation for enhanced phosphate and nitrate removal from agricultural wastewater - Yared Endale; Abreham Bekele Bayu; Zerihun Asmelash Samuel; Seifu Kebede; Eliza Kulbat (Scientific African)
This present study explores a wastewater treatment process through an alum-watermelon seed coagulant that can help alleviate the Gibe River nutrient impact, which has been adversely affected by agricultural runoff. Various ratios of alum to watermelon seed powder were tested, i.e., 1:3, 3:1, and 1:1. The results indicated that 1:3 was the best ratio and had efficiencies of removal 98.28 % for phosphate, 98.92 % for nitrate, 98.27 % for total dissolved solids, 96.11 % for biochemical oxygen demand, and 95.29 % for chemical oxygen demand. Maximum efficiencies were found at pH 3, 0.4 g/L dosage, 15 minutes contact time, and 40 minutes settling time. The results show that the watermelon seed coagulant blended with commercial alum at a ratio of 1:3 is the ideal blend for wastewater treatment of the highly contaminated Gibe River. The treatment not only improves the removal of the major pollutants but is also an eco-friendly and low-cost wastewater treatment process.